Trichoderma harzianum and Bacillus subtilis in Association with Rock Powder for the Initial Development of Maize Plants - Silva, Pedro Henrique Vinha [UNESP]; Souza, Ane Gabriele Vaz [UNESP]; de Araujo, Lilian Dutra [UNESP]; Frezarin, Edvan Teciano [UNESP]; de Souza, Gabriel Vinicius Lima [UNESP]; da Silveira, Cesar Martoreli; Rigobelo, Everlon Cid [UNESP] (MDPI, 2023)
Agricultural production currently faces many challenges worldwide, mainly due to its dependence on high amounts of input for food production, which may cause many environmental issues. The present study evaluated whether the inoculation of Bacillus subtilis, Trichoderma harzianum, and rock powder into the soil would benefit soil fertility and plant growth in vase conditions. The results showed that soil fertility for some nutrients increased, such as phosphorus, iron, sulfur, calcium, and potassium. The results also showed that plant parameters related to plant growth, such as plant height, leaf area, shoot dry matter (SDM), and root dry matter (RDM) increased with the inoculation of the microorganisms coupled with rock powder into the soil, even with 50% of the chemical fertilization dose compared to their control treatments. The findings showed potential benefits to soil fertility and plants with the inoculation of B. subtilis and the fungus T. harzianum in maize plants coupled with the application of rock powder to the soil. This study concludes that there is evidence that inoculating with microorganisms and applying rock powder could reduce the amount of chemical fertilizer needed. However, many years of field research are needed to verify the real contribution of this practice to sustainable agriculture.
Keywords: nutrient availability; plant growth promoters; soil fertilization; soil recovery